Design and Economic Evaluation of a Photovoltaic Water Pumping System for Tomato Irrigation in El Oued - Rehouma , Youssef . Yasmine , Amara.Danoune , Mohamed Bilal . Gougui Abdelmoumen. Naoui,Mohamed (University of Eloued جامعة الوادي, 2024)
This paper explores the design, economic assessment, and operation of a photovoltaic water pumping system for irrigating tomatoes in Terifaoui, El Oued, Algeria. Terifaoui's desert climate and lack of grid access make it a suitable candidate for a solar-powered irrigation system. The system design, simulated using PVsyst software, considers El Oued's climate to ensure reliable operation. This study examines the technology, economics, and operational aspects of the system, highlighting its potential to boost agricultural output and regional economic resilience
Article
Keywords: Photovoltaic; Renewable Energy; Solar-powered Sustainable; Water management.